A QUALIFICAÇÃO E A INSERÇÃO NO MUNDO DO TRABALHO DA PESSOA PORTADORA DE DEFICIÊNCIA: UM ESTUDO SOBRE O IMPACTO DA EXTINÇÃO DA LEI 6.297/75 - Castaldi, Marcia da Silva Dias (2009)
This study aims to analyze the difficulties faced by both companies to fulfill the Law of Quotas, as well as of Persons with Disabilities (PPD) to be inserted in the labor market due to lack of qualifications of candidates. Through literary research it became clear that our legislation demonstrates quite clearly that the legislature intended to ensure PPDs, the minimum participation influential in the active life of Brazilian society and an unprecedented advance, they have created the basic lines of the integration process poor society and market national production. It was also that companies are seeking professionals from among the universe of PPDs, already qualified, which usually are not. Private Organizations has also developed some projects for the qualification of PPDs. The Law 6297/75 that guarantee companies the discount on the IR double spending on training, was abolished on 12 December 1990. Companies need a financial incentive for them to deal with the qualification of these professionals, not as a burden but as a social project. If companies were benefiting from tax incentives, as they were in the presence of this law, companies would have a different view at the hiring of PPD? The research methodology includes a literature survey and an exploratory survey to be made in private companies, institutions that aim to help insert the PPDs and Private organizations. It has been found through research that there is concern by all those involved in finding effective means to ensure the inclusion of PPD in the labor market, although the lack of qualification is still a major problem. The creation of laws similar to the Law 6297/75 was identified as a great help to companies, since they were imposed that responsibility.(AU)